2023
DOI: 10.3390/ma16041442
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Dispersibility of TiO2 in the Colloidal System Using Trifunctional Spherosilicates

Abstract: Titanium dioxide is a commonly used ingredient in cosmetics acting as a thickening agent and inorganic UV filter. However, TiO2 is difficult to disperse, which causes problems in spreading the formulations. The solution to this problem is to modify the titanium dioxide surface to change its properties by creation of the new type of hybrid inorganic–organic UV filter. Therefore, this study aimed to functionalize titanium dioxide with organosilicon compounds and determine how this modification will affect the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Gao et al reported the synergistic photothermal/SDT of titania-coated Au nanoplates in cancer treatment [20]. Despite these achievements in the combination of noble metals and TiO 2 NPs for SDT, factors such as agglomeration [21][22][23][24] or adsorb protein [25,26], and hypoxia in tumor site [27] can alter the physicochemical properties of Au@TiO 2 and hindering their therapeutic effects. Therefore, constructing delivery systems with oxygencarrying abilities, good dispersion and high ROS production of Au@TiO 2 in a biological environment is still a challenge in SDT field.…”
Section: Introductionmentioning
confidence: 99%
“…Gao et al reported the synergistic photothermal/SDT of titania-coated Au nanoplates in cancer treatment [20]. Despite these achievements in the combination of noble metals and TiO 2 NPs for SDT, factors such as agglomeration [21][22][23][24] or adsorb protein [25,26], and hypoxia in tumor site [27] can alter the physicochemical properties of Au@TiO 2 and hindering their therapeutic effects. Therefore, constructing delivery systems with oxygencarrying abilities, good dispersion and high ROS production of Au@TiO 2 in a biological environment is still a challenge in SDT field.…”
Section: Introductionmentioning
confidence: 99%
“…Their unique cube-like structure creates a three-dimensional space, consisting of an inorganic core and attached organic functional groups [ 1 , 2 , 3 , 4 ]. Modifying the functional groups of these compounds allows one to adjust the product’s properties by synthesis [ 5 , 6 , 7 ]. Typically, functionalization occurs through catalytic reactions like hydrosilylation, silylative coupling, and metathesis [ 8 , 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, hybrids have been successfully used for various stable inorganic colloids free from aggregation, such as titanium oxide, zinc oxide, magnetic and metal nanoparticles. Miniemulsion polymerization is one of the common methods for preparing polymer hybrids in colloid systems [12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%